Replicative Fitness of a SARS-CoV-2 20I/501Y.V1 Variant from Lineage B.1.1.7 in Human Reconstituted Bronchial Epithelium - Franck Touret (American Society for Microbiology, 2021)
ABSTRACT Since its emergence in 2019, circulating populations of the new coronavirus (CoV) continuously acquired genetic diversity. At the end of 2020, a variant named 20I/501Y.V1 (lineage B.1.1.7) emerged and replaced other circulating strains in several regions. This phenomenon has been poorly associated with biological evidence that this variant and the original strain exhibit different phenotypic characteristics. Here, we analyze the replication ability of this new variant in different cellular models using for comparison an ancestral D614G European strain (lineage B1). Results from comparative replication kinetics experiments in vitro and in a human reconstituted bronchial epithelium showed no difference. However, when both viruses were put in competition in human reconstituted bronchial epithelium, the 20I/501Y.V1 variant outcompeted the ancestral strain. All together, these findings demonstrate that this new variant replicates more efficiently and may contribute to a better understanding of the progressive replacement of circulating strains by the severe acute respiratory CoV-2 (SARS-CoV-2) 20I/501Y.V1 variant. IMPORTANCE The emergence of several SARS-CoV-2 variants raised numerous questions concerning the future course of the pandemic. We are currently observing a replacement of the circulating viruses by the variant from the United Kingdom known as 20I/501Y.V1, from the B.1.1.7 lineage, but there is little biological evidence that this new variant exhibits a different phenotype. In the present study, we used different cellular models to assess the replication ability of the 20I/501Y.V1 variant. Our results showed that this variant replicates more efficiently in human reconstituted bronchial epithelium, which may explain why it spreads so rapidly in human populations.